Reading Genesis: ten methods - Hendel, Ronald S. (Cambridge Univ. Press, 2010)
"Reading Genesis presents a panoramic view of the most vital ways that Genesis is approached in modern scholarship. Essays by ten eminent scholars cover the perspectives of literature, gender, memory, sources, theology, and the reception of Genesis in Judaism and Christianity. Each contribution addresses the history and rationale of the method, insightfully explores particular texts of Genesis, and deepens the interpretive gain of the method in question. These ways of reading Genesis, which include its classic past readings, map out a pluralistic model for understanding Genesis in - and for - the modern age"--Provided by publisher